500 figures in clay : ceramic artists celebrate the human form - Gunter, Veronika Alice; Lark Books (New York : Lark Books, 2004)
From the Publisher: It's an absolutely unequaled photographic gallery: no other book has ever presented such a varied, captivating collection of contemporary ceramics based on the human form. The works range from representational to abstract, from artful realism to provocative surrealism, and many of them come from leaders in the field such as Judy Fox, Kurt Weiser, and Andy Nasisse. Kay Yourist has produced female forms that are smooth, minimalist vessels with only the slightest hint of breasts and belly. The simple, rounded features of Diane Lublinski's black-and-white figures possess a fun, clown-like whimsy. Michael A. Prather's mournful ceramic portraits have frowning faces and pointed dunce-like heads in a muted color palette. Many of the ceramics come with detail images and illuminating artist's commentary.
Introduction --Figures --Heads and busts --Torsos --Body details --Figurines and statues --Couples and multiples --Caricature --Metamorphosis --Two dimensional works --Acknowledgments --Artists index.
Includes index.
Keywords: Figure sculpture -- 20th century; Figure sculpture -- 21st century; Ceramic sculpture -- 20th century; Ceramic sculpture -- 21st century